Medium-term to long-term multi-objective renewable energy portfolio planning using Monte Carlo optimization - Jalocon, Clares Loren C.
The resources necessary in energy generation are high-valued and time-bound and strategically allocating them through generation planning is of great importance. Most generation planning models only account for limited criteria which focus on economic factors. The environmental and policy aspects which are main considerations among decision-makers are meagerly reflected in these models. The study performed renewable energy portfolios planning through a Monte-Carlo optimization approach specifically, the Cross Entropy method. The renewable energy portfolio planning was applied to the Philippine setting considering multiple factors composed of economic and environmental metrics. The economic criteria shall include but not limited to capital and production costs. The corresponding cost for the emissions will serve as the metric of the environmental impact. Policy mechanisms for the Renewable Energy (RE) Program such as the Renewable Portfolio Standards (RPS) and carbon caps were also incorporated in the model. With varying scenarios for the factors and policy mechanisms, the study yielded the corresponding investment and operation schedules for the generating plants. The investment and generation schedules for the Philippine setting based on recent policy developments of the RE program were also simulated using the generation planning model.